Corneal Disease Recent Developments in Diagnosis and Therapy - Reinhard, Thomas; Larkin, Frank; SpringerLink (Online service) (Berlin, Heidelberg : Springer Berlin Heidelberg : Imprint: Springer, 2013)
This book, written by leading clinicians and scientists, focuses on recent clinically relevant advances in the diagnosis and treatment of corneal disorders. After an opening chapter considering the latest knowledge on the heredity of keratoconus, important advances in corneal imaging are discussed, in particular the use of optical coherence tomography and in vivo confocal microscopy for evaluation of the normal and the diseased cornea. Antiangiogenic treatment options are then reviewed, and new aspects in the diagnosis and therapy of mycobacterial keratitis explained. Further chapters address the storage of donor cornea for penetrating and lamellar keratoplasty and the keratoplasty in infants. The book closes by discussing new developments in antibacterial chemotherapy for bacterial keratitis.
New aspects in diagnosis and therapy of mycobacterial keratitis -- New developments in antibacterial chemotherapy for corneal Infection -- Heredity of keratoconus -- Advances in corneal imaging -- An update on anti-angiogenesis in the cornea -- Storage of penetrating and lamellar grafts -- Keratoplasty in infants.
Keywords: Medicine; Ophthalmology; Medicine & Public Health; Ophthalmology